2001
DOI: 10.1016/s0042-6989(00)00310-2
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement control in reading: word predictability has little influence on initial landing positions in words

Abstract: We examined the initial landing position of the eyes in target words that were either predictable or unpredictable from the preceding sentence context. Although readers skipped over predictable words more than unpredictable words and spent less time on predictable words when they did fixate on them, there was no difference in the launch site of the saccade to the target word. Moreover, there was only a very small difference in the initial landing position on the target word as a function of predictability when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
99
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 34 publications
17
99
0
4
Order By: Relevance
“…In our experiments we clearly show that the saccade targeting system is not overly sensitive to even a large difference in initial bigram frequency of upcoming words, when these initial bigrams are of relatively high, or extremely high, frequency. Coupled with previous findings showing no evidence for modulation of saccade length or initial fixation location because of target words' predictability (e.g., Rayner et al, 2001), or only effects of modest size for initial letter sequence and morphological properties (e.g., Hyönä, 1995;White & Liversedge, 2004;2006;Yan et al, 2014), we may conclude that the saccade targeting system is minimally influenced by the linguistic properties of the upcoming words.…”
Section: Ge Ne Ralndiscussionsupporting
confidence: 87%
“…In our experiments we clearly show that the saccade targeting system is not overly sensitive to even a large difference in initial bigram frequency of upcoming words, when these initial bigrams are of relatively high, or extremely high, frequency. Coupled with previous findings showing no evidence for modulation of saccade length or initial fixation location because of target words' predictability (e.g., Rayner et al, 2001), or only effects of modest size for initial letter sequence and morphological properties (e.g., Hyönä, 1995;White & Liversedge, 2004;2006;Yan et al, 2014), we may conclude that the saccade targeting system is minimally influenced by the linguistic properties of the upcoming words.…”
Section: Ge Ne Ralndiscussionsupporting
confidence: 87%
“…The predictions of E-Z Reader were very close those values: 37% of predictable words and 25% of unpredictable words were skipped. The difference between predictable and unpredictable words (9% in our study and 12% for E-Z Reader) is quite consistent with prior research (Rayner et al 2001;Rayner & Well, 1996). However, inconsistency was observed in the pattern of results for fixation times (Table 1).…”
supporting
confidence: 91%
“…E-Z Reader did not predict the effect of predictability on first fixation duration and single fixation. With respect to gaze duration, the effect predicted by E-Z Reader was comparable in size to the effect obtained in other studies (Rayner et al 2001;Rayner & Well 1996), though it was lower than in our study. A closer examination of the data indicated that the prediction of E-Z -rReader was inconsistent for high frequency words: Fixation duration was longer for predictable than for unpredictable words (Table 2).…”
supporting
confidence: 80%
“…Reaction times as well as eye movement data point to faster processing of high than of low predictability words (e.g., Ashby, Rayner, & Clifton, 2005;Calvo & Meseguer;Duffy, Henderson, & Morris, 1989;Ehrlich & Rayner, 1981;Fischler & Bloom, 1979;Kleiman, 1980;Kliegl et al, 2004Kliegl et al, , 2006Rayner, Ashby, Pollatsek, & Reichle, 2004;Rayner, Binder, Ashby, & Pollatsek, 2001;Rayner & Well, 1996;Schuberth & Eimas, 1977;Stanovich & West, 1983;West & Stanovich, 1982). The critical question, however, is when does top-down expectation of a stimulus interact with the incoming visual information during reading and, depending on whether the prediction was correct or wrong, when does it help or hurt word processing?…”
Section: Predictability: Top-down Expectationsmentioning
confidence: 99%